Penatalaksanaan Anestesi Pasien Tetralogy of Fallot pada Operasi Mouth Preparation - Arsy Felisita Dausawati; Iwan Fuadi (Faculty of Medicine, Universitas Padjadjaran, 2013)
Tetralogy of Fallot (TOF) merupakan kelainan jantung bawaan yang terdiri atas ventricular septal defect, overriding aorta, stenosis pulmonal, dan hipertrofi ventrikel kanan. Tetralogy of Fallot termasuk kelainan jantung bawaan tipe sianotik. Seorang anak laki-laki 9 tahun datang untuk perawatan dan pencabutan gigi sebagai persiapan untuk operasi koreksi TOF di Rumah Sakit Dr. Hasan Sadikin Bandung pada Februari 2012. Anamnesis didapatkan riwayat kebiruan sejak bayi dan pada pemeriksaan fisis didapatkan anak yang tampak sianosis, SpO2 70–75%, murmur sistol, dan jari tabuh. Pada pemeriksaan ekokardiografi didapatkan kelainan TOF. Manajemen anestesi pada pasien ini dilakukan dengan menggunakan ketamin dan vekuronium untuk induksi serta pemeliharaan dengan O2, N2O, dan halotan. Serangan sianotik dapat terjadi preoperatif, intraoperatif, dan pascaoperatif yang diatasi dengan meningkatkan systemic vascular resistance (SVR) dibandingkan dengan pulmonary vascular resistance (PVR). Simpulan, prinsip pengelolaan perioperatif pembedahan nonkardiak pada pasien tetralogy of Fallot (TOF) adalah mencegah terjadi peningkatan shunt dari kanan ke kiri dengan menjaga agar tidak terjadi penurunan SVR, peningkatan PVR, dan menurunkan spasme infundibular.Kata kunci: Kelainan jantung kongenital sianotik, pulmonary vascular resistance (PVR), systemic vascular resistance (SVR), tetralogy of Fallot (TOF)Management of Anesthesia in Patients Tetralogy of Fallot which Undergo Mouth PreparationTetralogy of Fallot (TOF) is a congenital heart disease consisting of a ventricular septal defect, overridingaorta, pulmonary stenosis and right ventricular hypertrophy. Tetralogy of Fallot, including the type of cyanotic congenital heart defects. A boy of 9 years came for treatment and tooth extraction as preparation for the surgical correction of TOF at the Dr. Hasan Sadikin Hospital-Bandung whitin February 2012. Patients with a history of blue as a baby, and on physical examination found the child looking cyanosis, SpO2 70–75%, systolic murmur and finger clubbing. Abnormalities on echocardiography obtained TOF. Anesthetic management of these patients was performed using ketamine and vecuronium for induction and maintenance with O2, N2O and halothane. Cyanotic attacks can occur preoperative, intraoperative and postoperative, who treated by increasing systemic vascular resistance (SVR) compared to pulmonary vascular resistance (PVR). In conclusions, perioperatif mangement principal for non cardiac surgery on tetralogy of fallot (TOF) is to prevent shunting from right to left by keep the SVR from decline, increase on PVR, and reduce infundibular spasme.Key words: Cyanotic congenital heart defects, pulmonary vascular resistance (PVR), systemic vascular resistance (SVR), tetralogy of Fallot (TOF) DOI: 10.15851/jap.v1n2.123